INCREASING STUDENTS’ WRITING SKILL THROUGH PEER EDITING TECHNIQUE TO THE SECOND SEMESTER OF IKIP PGRI BOJONEGORO - Fitri Nurdianingsih (LPPM Press STKIP PGRI Pacitan, 2016)
This research is aimed to know whether the use of Peer editing technique can improve writing skill of the second semester students English Department at IKIP PGRI Bojonegoro in academic year 2015/2016. This study was conducted through an action research. The writer applied two cycles of action research. She began her study by giving a pre-test, cycle 1, cycle 2, and a post-test. To collect the data, the writer used test only as her research instrument. Based on the finding result, it showed that the students’ improvement in mastering English writing especially in writing an essay was good. The average achievement of the students’ pre-test was 43,33, in cycle 1 was 52,11, in cycle 2 was 65,44, and the post-test was 76,67. The main factor affecting the improvement was the students’ interest in the material given that was the peer-editing technique. The writer concludes that the students got positive behaviour in writing an essay after appling peer editing technique. They could be more confident and active while they did the peer-editing technique. It is suggested that using peer-editing technique should be recommended for teaching writing especially an essay.